A Link between Psychopathy Affect and Instrumentality in Homicide - Sohn, Ji Seun (Homicide studies, 2022)
This study tests the hypothesis that psychopathy is more associated with instrumental homicides than mixed and reactive homicides, and explores relationships between Psychopathy Checklist-Revised (PCL-R) facet/item scores and different forms of homicide: instrumental (n = 130), mixed (n = 103), and reactive (n = 219) homicides. Instrumental homicides scored higher on facet 2 (p < .01) but scored lower on facet 4 (p < .1) compared to reactive homicides, whereas no facet scores differed between mixed and reactive homicides. Among the items of facet 2 (affective), remorselessness (item 6), and callousness (item 8) were predictive of instrumental homicide.